P05.13 Prevalence and anatomical distribution of mycoplasma genitalium macrolide resistance markers from subjects enrolled in a multi-centre us clinical study. (13th September 2015) - Getman, D; O'Donnell, M; Cohen, S; Jiang, A
Abstract : Introduction: This study evaluated the prevalence and anatomical distribution of Mycoplasma genitalium (Mgen) 23s rRNA mutations (23s-MTs) conferring macrolide resistance among male and female subjects enrolled in a prospective multi-site US clinical study. Methods: Specimens obtained from symptomatic and asymptomatic men and women enrolled from 7 diverse US clinical sites, including obstetrics and gynaecology, family planning, public health, and sexually transmitted disease clinics, were tested using a research TMA assay for Mgen (Hologic, Inc.) on the DTS System or TIGRIS DTS System. Samples positive for Mgen by TMA were evaluated by nested PCR or RT-PCR and Sanger sequencing of Mgen 23S rRNA to identify the presence of macrolide resistance mutations at position 2058 (A2058G, A2058C, A2058T) or position 2059 (A2059G). Results: Of 50 male subjects with Mgen 23s rRNA sequence results, 21 (42%) contained 23s-MTs. Slightly more 23s-MTs were found in urethral swabs vs male urine samples (44.8% vs 36.7%, respectively). For female subjects, 65 of 128 (50.8%) harboured 23s-MTs, with higher prevalence found in vaginal swab samples (50.2%) compared to urine (46%), Thinprep liquid Pap (41.7%), and endocervical swabs (37.8%). Sequencing of samples collected from anatomically distinct female urogenital sites (vagina, cervix, urine) revealed 18 of 35 (51.4%) subjects had a unique complement of Mgen 23s-MT and/or wild-type sequences at each anatomic site. For male subjects with both urine and urethral swab samples, 3 of 9 (33.3%) subjects had unique Mgen 23s-MT/WT sequences in each sample type. Conclusion: Mgen strains harbouring 23s rRNA-mediated macrolide resistance phenotypes were highly prevalent in this US cohort of male and female subjects. Detection of different macrolide-resistant Mgen strains in samples collected from different anatomical locations suggests that previous estimates for resistance rates that relied on a single anatomical site sample collection may have underestimated the extent of Mgen macrolide resistance in the population. Disclosure of interest statement: D Getman, M O'Donnell, and A Jiang are scientists employed by Hologic. S Cohen is a student at Occidental College and a summer intern at Hologic.